The Effects of Insertion Approach on the Stability of Dental Implants - Yuan-Yang Hsu; Heng-Li Huang; Lih-Jyh Fuh; Ming-Tzu Tsai; Jui-Ting Hsu (Applied Bionics and Biomechanics)
Dental implant surgery involves the insertion of a dental implant into the alveolar bone; the success of the surgery depends on the initial stability of the implant. The objective of this study was to examine the effects of dental implant insertion approaches in clinical surgery and in accordance with the standards of American Society for Testing and Materials on initial implant stability. Three insertion approaches were used for dental implant placement (Branemark Systems NobelSpeedy Groovy, Nobel Biocare AB, Gothenburg, Sweden) in two types of artificial bone—good bone (GB) and poor bone (PB). The three insertion approaches were as follows: (1) continuous rotation insertion (CRI): using a torque testing machine to continuously screw in an implant to completion and (2 and 3) intermittent rotation insertion (IRI)_90 and IRI_80: using CRI to bury an implant to 90% and 80% of its full length followed by IRI to complete the implantation, respectively. The maximum insertion torque value (ITV), periotest value (PTV), and implant stability quotient (ISQ) were measured and compared. The results indicated that bone quality and insertion approach both affected implant stability. Insertion approaches affected all three implant stability indicators differently in the GB and PB groups (p=0.008). In GB groups, the insertion approach primarily affected ITV, whereas in PB groups, it primarily affected PTV. The effect of the insertion approach was less apparent for ISQ. Overall, in both the GB and PB groups, the implant stability for IRI_80 was greater than that for IRI_90, and the implant stability for IRI_90 was greater than that for CRI. Future in vitro studies should adopt an insertion approach that complies with the clinical practice for dental implant surgery. Dentists should adjust the timing for IRI in dental implant surgery to achieve greater initial dental implant stability.